Management of soil and tuber borne diseases of potato - Sagar, Vinay (Indian Horticulture, 2020)
Several soil and tuber borne diseases are known to affect potato and result in heavy losses. These diseases not only reduce quality and market value of the produce but also spread to new un-infested fields through infected seed potato tubers. Diseases such as black scurf, common scab and powdery scab disfigure potato tubers and reduce their market value whereas dry rots, charcoal rots and soft rots spoil the harvested produce during storage causing significant losses. Potato wart is a serious disease which once established is difficult to eradicate and thus require quarantine measures. Bacterial wilt or brown rot of potato is another serious disease which has threatened potato cultivation in many potato growing areas of the world including India. The article discusses important soil and tuber borne diseases, and their management in brief.